Redefining cardiovascular risk stratification: The evolving role of coronary CTA - Kamila, Putri Annisa (Heart Science Journal, 2025)
Coronary computed tomography angiography (CCTA) has evolved far beyond its initial role as an anatomical imaging modality. Today, it serves as a versatile, multiparametric tool for cardiovascular risk assessment. This progress has been driven by advances in plaque characterization, non-invasive functional assessment, coronary inflammation imaging, and artificial intelligence (AI). CCTA enables clinicians not only to detect obstructive coronary artery disease but also to evaluate total plaque burden and high-risk plaque characteristics, such as low-attenuation components and positive remodeling. The addition of fractional flow reserve derived from CCTA (FFR-CT) offers myocardial ischemia assessment without the need for invasive testing. More recently, the perivascular fat attenuation index (FAI) has emerged as a promising marker of coronary inflammation, highlighting patients who may have residual inflammatory risk despite non-obstructive disease. AI-driven tools, including models like AI-QCTISCHEMIA, now allow for automated and accurate plaque analysis and ischemia prediction. The advent of photon-counting detector CT (PCD-CT) complements these advancements by improving spatial resolution and visualization of vulnerable plaque. These developments are reshaping the role of CCTA in clinical practice—from a diagnostic test to an integrated platform for individualized cardiovascular prevention and management.